2005
DOI: 10.1016/j.febslet.2005.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for HIV Tat upregulation of IL‐10 and other cytokine expression: Kinase signaling and PKR‐mediated immune response

Abstract: HIV Tat has been known to have multiple regulatory roles including replication of HIV and modulation of cellular kinases. We investigated whether signaling kinase PKR plays a critical role in mediating Tat-induced cytokine dysregulation. We showed Tat induction of IL-10 dysregulation is associated with PKR activation. To examine the mechanism involved, inhibition of PKR activity abrogated the Tat-induced cytokine induction. We next identified that the MAP kinases including ERK-1/2 and p38 are downstream of PKR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 30 publications
(38 reference statements)
4
56
0
1
Order By: Relevance
“…The PKR inhibitor 2-AP almost totally abolished IL-10 mRNA induction in murine macrophages (Fig. 4), consistent with the reported role for PKR in IL-10 induction in human PBMC by HIV-Tat stimulation (54). Consequently, S100A8 mRNA and protein levels were also reduced (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…The PKR inhibitor 2-AP almost totally abolished IL-10 mRNA induction in murine macrophages (Fig. 4), consistent with the reported role for PKR in IL-10 induction in human PBMC by HIV-Tat stimulation (54). Consequently, S100A8 mRNA and protein levels were also reduced (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…HIV-1 requires the cellular receptor CXCR4 (X4-tropic virus) or CCR5 (R5-tropic virus) for entrance into host epithelial cells (31). Using immunofluorescence microscopy, we were unable to detect either CXCR4 or CCR5 in our cultured human cholangiocytes, while control HT29 cells, which are susceptible to HIV-1 in- (Fig.…”
Section: H69 Cells Do Not Express Hiv-1 Coreceptorsmentioning
confidence: 70%
“…Tat is essential for replication of the viral genome, and it has been proposed that Tat is an important factor in HIV-induced pathogenesis of AIDS (2). Exogenous Tat has a variety of effects on cellular processes in uninfected cells, including increased binding of nuclear factor kappa B (NF-B) to DNA, increased production of cytokines, increased expression of cytokine receptors, and modulation of cell survival and proliferation (2,19,31,34,42). Furthermore, studies have demonstrated that Tat increases apoptosis in a variety of cell types, including cell types not directly infected by HIV-1 (4,42).…”
mentioning
confidence: 99%
“…Although results from several studies strongly indicate Tat as a potential vaccine candidate, some studies show an immunosuppressive role of Tat, particularly against the coimmunogens, in the host (18,19). In addition, studies from patients have indicated an increase in IL-10 production from infected cells (20) and Tat has been implicated in such IL-10 induction (21,22). IL-10 is known to inhibit a broad spectrum of cellular immune responses.…”
Section: Hiv-1 Tat Suppresses Gp120-specific T Cell Response In Il-10mentioning
confidence: 99%